5-fluorouracil and cardiotoxicity: a review. (16th June 2018) - Sara, Jaskanwal D.; Kaur, Jasvinder; Khodadadi, Ryan; Rehman, Muneeb; Lobo, Ronstan; Chakrabarti, Sakti; Herrmann, Joerg; Lerman, Amir; Grothey, Axel
Fluoropyrimidines such as 5-fluorouracil (5-FU) form the foundation of a wide variety of chemotherapy regimens. 5-FU is in fact the third most commonly used chemotherapeutic agent in the treatment of solid malignancies across the world. As with all chemotherapy, balancing the potential benefits of therapy against the risks of drug-related toxicity is crucial when clinicians and patients make shared decisions about treatment. 5-FU is the second most common chemotherapeutic drug associated with cardiotoxicity after anthracyclines, which can manifest as chest pain, acute coronary syndrome/myocardial infarction or death. Nevertheless a widespread appreciation of 5-FU-related cardiotoxicity and its implications is lacking amongst clinicians. In this review, we outline the incidence, possible risk factors, and likely pathophysiological mechanisms that may account for 5-FU-related cardiotoxicity and also highlight potential management strategies for this poorly understood clinical entity.